Retinal Proteomics of a Mouse Model of Dystroglycanopathies Reveals Molecular Alterations in Photoreceptors - Uribe, Mary Luz (J Proteome Res, 2021)
[Image: see text] Mutations in the POMT1 gene, encoding a protein O-mannosyltransferase essential for α-dystroglycan (α-DG) glycosylation, are frequently observed in a group of rare congenital muscular dystrophies, collectively known as dystroglycanopathies. However, it is hitherto unclear whether the effects seen in affected patients can be fully ascribed to α-DG hypoglycosylation. To study this, here we used comparative mass spectrometry-based proteomics and immunofluorescence microscopy and investigated the changes in the retina of mice in which Pomt1 is specifically knocked out in photoreceptor cells. Our results demonstrate significant proteomic changes and associated structural alteration in photoreceptor cells of Pomt1 cKO mice. In addition to the effects related to impaired α-DG O-mannosylation, we observed morphological alterations in the outer segment that are associated with dysregulation of a relatively understudied POMT1 substrate (KIAA1549), BBSome proteins, and retinal stress markers. In conclusion, our study provides new hypotheses to explain the phenotypic changes that are observed in the retina of patients with dystroglycanopathies.